If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2(x + 2) = (2x + 15) Reorder the terms: 5x + -2(2 + x) = (2x + 15) 5x + (2 * -2 + x * -2) = (2x + 15) 5x + (-4 + -2x) = (2x + 15) Reorder the terms: -4 + 5x + -2x = (2x + 15) Combine like terms: 5x + -2x = 3x -4 + 3x = (2x + 15) Reorder the terms: -4 + 3x = (15 + 2x) Remove parenthesis around (15 + 2x) -4 + 3x = 15 + 2x Solving -4 + 3x = 15 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 3x + -2x = 15 + 2x + -2x Combine like terms: 3x + -2x = 1x -4 + 1x = 15 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 1x = 15 + 0 -4 + 1x = 15 Add '4' to each side of the equation. -4 + 4 + 1x = 15 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = 15 + 4 1x = 15 + 4 Combine like terms: 15 + 4 = 19 1x = 19 Divide each side by '1'. x = 19 Simplifying x = 19
| (y+2)9= | | 2n+3.3=-4.064-1.44n | | x+4=2m-nx | | 2(x+8)=2(2x+1) | | x+4x=(3x+54) | | 0.11x+1.5=2.49 | | -6x-3(-4x-18)=90 | | 6x-12=4x-26 | | 3a+14=42-a | | 2y=8x-4 | | 24=-3x-18 | | 4+3x=3-5x | | 60+5x=135-10x | | 6(h+5)=66 | | 6(h+5)=66 | | Y-4x=13 | | 7(7c+1)-4c=13(3-2) | | 3x+10+2x=2(x+8) | | -(-4x-1)=5 | | 13=65x | | 3(x+2)+2x=46 | | 8x+=2x-7 | | 40-8+12= | | 4(y-5)=6y-18 | | 2h+12=5h | | 2x+x+12=78 | | 6(v-9)=4(v-9) | | 5x+11=2x+5 | | y=0.499x-974.1 | | 80x+100=70x+250 | | 8=4(r+8) | | t+t/8+t-30=259 |